Germination of bean cultivars with contrasting physical characteristics under osmotic stress conditions - Aguilar Benítez, Gisela; Vázquez Díaz, Estefanía Grizel; Castro Rivera, Rigoberto; Cruz Crespo, Elia; Jarquin Gálvez, Ramón (Revista Mexicana de Ciencias Agrícolas, 2019)
The cultivation of common bean (Phaseolus vulgaris L.) in Mexico occupies the third place by established surface, although the production reports annual variations due to the heterogeneity of the climatic conditions in which it is produced. Given the cultural and nutritional importance of this legume, farmers and geneticists have selected cultivars with desirable culinary characteristics and adaptations to restrictive environments. The objective was to characterize the germination of bean cultivars collected in the Central Valleys of Oaxaca and the Potosino Altiplano, regions with contrasting environments and culture. In the Phytochemistry laboratory of the Desert Areas Research Institute, during the summer of 2015, five traditional cultivars and ten improved bean cultivars were evaluated. The percentage of germination was quantified with the procedures of the standard test described by ISTA (2005) and the seeds that showed lower incidence of fungal contamination and higher percentage of germination were selected. With four improved cultivars and four traditional cultivars, the average weight of a sample of 100 seeds and the proportion of seminal structures were determined. The effect of three osmotic potentials on germination was also recorded (Ψo: 0, -0.5 and -1.1MPa). Differences (p≤ 0.05) were observed in the weight of 100 seeds, the percentage of the testa and the embryonic axis. In Ψo: 0.0 Mpa and -0.5 Mpa, differences were obtained (p≤ 0.05) among the cultivars evaluated. In Ψo: -1.1 Mpa germination was null in all cultivars.
Keywords: creole; Mesoamerican; races